Penerapan Prinsip Ergonomi: Studi pada Gedung A Fakultas Pertanian Universitas Malikussaleh - Liza Adyani; Husnul Fitri (Jurnal Psikologi Terapan, 2019)
A building with lots of rooms and beds will all be more beautiful and harmonious if the decor is tailored to the needs of workers or employees. This study aims to analyze and interpret the room settings of a building based on ergonomic principles. The method used in this study is a survey method with observation data collection techniques, both physical and psychological. The results of the study show that in general agriculture A campus doesn’t reflect ergonomic principles, only dosenn rooms and study rooms meet the ergonomic principle criteria.